Gene mutations that promote adrenal aldosterone production, sodium retention, and hypertension - Moraitis AG; Rainey WE; Auchus RJ (The Application of Clinical Genetics, 2013)
Andreas G Moraitis,1 William E Rainey,1,2 Richard J Auchus1 1Division of Metabolism, Endocrinology, and Diabetes, Department of Internal Medicine, 2Department of Physiology, University of Michigan, Ann Arbor, MI, USA Abstract: Primary aldosteronism (PA) is the most common form of secondary hypertension, found in about 5% of all hypertension cases, and up to 20% of resistant hypertension cases. The most common forms of PA are an aldosterone-producing adenoma and idiopathic (bilateral) hyperaldosteronism. Rare genetic forms of PA exist and, until recently, the only condition with a known genetic mechanism was familial hyperaldosteronism type 1, also known as glucocorticoid-remediable aldosteronism (FHA1/GRA). FHA type 3 has now been shown to derive from germline mutations in the KCNJ5 gene, which encodes a potassium channel found on the adrenal cells. Remarkably, somatic mutations in KCNJ5 are found in about one-third of aldosterone-producing adenomas, and these mutations are likely to be involved in their pathogenesis. Finally, mutations in the genes encoding an L-type calcium channel (CACNA1D) and in genes encoding a sodium–potassium adenosine triphosphatase (ATP1A1) or a calcium adenosine triphosphatase (ATP2B3) are found in other aldosterone-producing adenomas. These findings provide a working model, in which adenoma formation and/or aldosterone production in many cases derives from increased calcium entry, which drives the pathogenesis of primary aldosteronism. Keywords: hyperaldosteronism, hereditary, potassium channel, calcium channel